Hydrodynamic Device Modeling with Band Nonparabolicity. Issue 1 (1998) - Cai, J.; Cui, H. L.; Lenzing, E. H.; Pastore, R.; Rhodes, D. L.; Perlman, B. S.
Abstract : A semiconductor device model based on a set of quantum mechanically derived hydrodynamic balance equations are presented. This model takes full account of band nonparabolicity, in addition to its other useful features such as the explicit evaluation of momentum and energy relaxation rates, in the form of frictional force and energy loss rate, within the model, and inclusion of carrier-carrier interaction effects, such as dynamical screening. Numerical results of one-dimensional device simulations are presented and compared with parabolic approximations.